Pengaruh Pengalaman Praktek Kerja Lapangan dan Ujian Kompetensi Kejuruan Terhadap Kesiapan Siswa Kelas XII AKT di SMK Keuangan Pekanbaru Untuk Memasuki Dunia Kerja - Hutabarat, Santi Agustina (Department of Accounting, Faculty of Economics & Business, 2025)
This study aims to analyze the influence of Practical Work Experience (PKL) and Vocational Competency Exams (UKK) on the readiness of 12th grade AKT students at SMK Keuangan Pekanbaru to enter the workforce. A quantitative approach was employed, involving 100 students selected through purposive sampling. Data were collected using validated and reliable questionnaires, then analyzed using multiple linear regression. The results showed that PKL experience had a positive and significant impact on students' job readiness, while UKK also significantly contributed. Simultaneously, both variables had a substantial effect on students' preparedness to enter the workforce. These findings highlight the importance of practical experience and competency mastery in enhancing vocational high school graduates' readiness to meet the demands of an increasingly competitive job market.